ANALISIS FEKUNDITAS DAN DIAMETER TELUR KERANG BAMBU (Solen lamarckii, Chenu 1843) DI ZONA INTERTIDAL DESA API-API KECAMATAN BANDAR LAKSAMANA KABUPATEN BENGKALIS - Langsana, Laila; Nasution, Syafruddin; Efriyeldi, Efriyeldi (Jurnal Perikanan dan Kelautan, 2020)
Bamboo clam (Solen lamarckii) is a type of mollusck of the Solenidae family known as “sepahat” by the people around Bengkalis. This study was conducted at Api-Api village waters, Bengkalis Regency  in January 2020. This study aims to investigate the fecundity produced by each female of  bamboo clam and egg diameter in each phase of maturity gonad stage. This study used survey method and sampling location determined by simple random sampling. Fecundity was calculated using the modificated volumetric method. The result showed, the fecundity of bamboo clam ranged from 290,325-1,902,391 with an average 1,105,285 ±1,074,724 eggs  for 50.3-72.8 mm in shell length. Egg diameter ranged between 30-110 μm. Average diameter in each phase of maturity gonad stage, the stage I gonads was 46.7 μm, stage II 65.2 μm, stage III 82.8 μm and stage IV 101 μm.